BRIDGING THE GAP: EFFORTS TO MINIMIZE EDUCATION GAPS THROUGH INCLUSIVE EDUCATION IN RURAL AREAS - Hidayat, Salman Ali; Nuruzzaman, Muhammad Adib (Sanata Dharma University Yogyakarta, 2024)
This study intends to explore the efforts to minimize the education gap between urban and rural areas through the implementation of inclusive education. This research uses qualitative methods with an oncoming literature study which is carried out to gain information from various literature sources that are relevant to the issue of inclusive education and educational disparity. The results show that inclusive education has the potential to address existing educational disparities between urban and rural areas. Inclusive education, by prioritizing the accessibility and participation of students with diverse backgrounds and needs, is an approach that promotes equity in education. Collaboration of various stakeholders such as the government, educational institutions, and local communities is important to support the implementation of inclusive education and overcome obstacles faced by students in rural areas. This research offers a foundation for policy recommendations and obvious actions to optimize the implementation of inclusive education as a concrete effort to bridge the education gap.